Beyond the Veil: Deconstructing Gender Activism and Islamic Identity in Post-Secular Public Spaces among Muslim Women in Indonesia - Setiyani, Wiwik; Hidayati, Nuril; Nurhairunnisa; Ubaidillah, M. Hasan (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
This study investigates how Muslim women navigate their Islamic identity, engage in gender activism, and operate within post-secular public spaces. By applying semiotic principles, it examines how female activists challenge traditional religious norms and societal expectations to develop polysemic expressions of Islamic identity. By interviewing and analyzing four leading Indonesian Muslim women activists, highlight how these women redefine their roles within religious and societal contexts through activism. Reshaping public perceptions of non-hijabi Muslim women activists. The findings reveal that; [1], gender is not a static category but something negotiated and shaped through actions and reinterpretation of identity in socio-religious contexts. It underscores the dynamic nature of activism, where hijab is reinterpreted not as a rigid religious mandate but as a fluid cultural mandate. [2], activists employ traditional and innovative markers to articulate their identities, challenging the hegemonic narrative imposed by religious and political authorities. The fact that Islamic identity coexists with modernity and inclusivity. In conclusion, this paper contributes to a nuanced understanding of the evolving roles of Muslim women activists. [Penelitian ini mengkaji bagaimana perempuan Muslim menavigasi identitas keislaman mereka, aktif sebagai aktitvis gender, dan di ruang publik pasca-sekuler. Dengan menerapkan prinsip semiotika, riset ini mempelajari bagaimana para aktivis perempuan menantang norma agama tradisional dan ekspektasi masyarakat guna mengeksplor ekspresi identitas Islam yang bersifat polisemik. Melalui wawancara dan analisis terhadap empat aktivis perempuan terkemuka Indonesia, penelitian menyoroti bagaimana para perempuan tersebut meredefinisi peran mereka dalam konteks agama dan sosial melalui aktivisme, sekaligus mendekonstruksi persepsi publik terhadap aktivis muslimah yang tidak berhijab. Temuan menunjukan: [1], gender bukan kategori statis, melainkan sesuatu yang bisa dinegosiasikan dan dibentuk melalui tindakan dan reinterpretasi dalam konteks socio-religious. Menegaskan bahwa aktivisme bersifat dinamis, dimana hijab tidak tidak lagi dimaknai sebagai kewajiban agama yang kaku tetapi mandat budaya yang fleksibel/luwes. [2], Para aktivis memanfaatkan simbol tradisional dan inovatif untuk mengartikulasi identitas mereka. Menantang narasi hegemoni otoritas agama dan politik. Karena sejatinya identitas Islam dapat berdampingan dengan modernitas dan inklusivitas. Pada akhirnya, paper ini berkonstribusi pada pemahaman yang lebih mendalam mengenai peran muslimah yang terus berkembang dalam aktivisme.]